Can Princesses Be Powerful? A Quasi-Experimental Study Examining Children's Perceptions of Princesses and the Self. Issue 1 (2nd January 2023) - Dinella, Lisa M.; Levinson, Jordan A.; Srouji, Maryam A.
Abstract: Children's gender schematic cognitions guide their attention, affinities, and behaviors, often narrowing their opportunities. The goal of the present study is to examine how children's exposure to animated Disney princesses modeling agentic behaviors (such as being a leader) alters children's gender schematic perceptions of princesses' characteristics, and if this exposure impacts children's perceptions of their own gender-typed qualities. Interviews with 60 children from the northeast region of the United States (Mage = 4.5 years old) at the beginning and end of six weeks indicate that, as hypothesized, children's perceptions of princesses and themselves became less gender schematic after cumulative exposure to animated videos depicting princesses modeling agentic behaviors. Children's perceptions of princesses' agency and their own agency increased throughout the study, asserting that with exposure to nontraditional gender-typed characters, children begin to see themselves as less gender-typed. These findings provide new insights into the role of early children's media exposure in shaping children's gender cognitions.